The Analysis of Relationship between Job Satisfaction and Working Environment of Teachers in Islamic Private School - Abdurrahman Sadikin; Erni Andriana; Abdul Manap; Akhmad Ramli; Hendrajaya Hendrajaya (Departement of Mathematics Education, 2023)
The goal of this study is to investigate how the workplace environment affects teachers' job satisfaction in junior high schools. Between October and November 2022, this study was undertaken. The study's independent variable was the workplace environment, while the dependent variable was teacher job satisfaction. With a quantitative approach, this research methodology employs the ex-post facto method. Random sampling is the method used for sampling. The research tool utilized was a questionnaire with five different options for answers and a Likert scale score. While the t test is employed as a hypothesis test for the regression technique. The alternative hypothesis (Ha) proposed is accepted based on the results of calculating the hypothesis with the t test between the work environment and teacher job satisfaction in junior high schools. The value of t-count > t-table (6.047 > 1.682) indicates that the work environment has a significant impact on teacher job satisfaction in junior high schools. The findings of calculating the coefficient of determination also demonstrate that, in junior high schools, the working environment contributes 46.5% to teacher job satisfaction. The work of teachers should be closely supervised by principals, who should also encourage them and reward their accomplishments, both material and non-material, to improve the level of job satisfaction among teachers.